(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
nflammatory lung diseases are among the most common causes of morbidity and mortality and are accompanied by the development of systemic and local inflammatory responses. This article reviews the main inflammatory markers used in the laboratory diagnosis of lung diseases and discusses their diagnostic and prognostic significance. Particular attention is given to indicators such as C-reactive protein, procalcitonin, interleukins, ferritin, and parameters of the complete blood count. The role of laboratory investigations in the differential diagnosis of bacterial and viral infections, assessment of inflammatory activity, monitoring of treatment effectiveness, and prediction of disease course is demonstrated. A comprehensive laboratory approach facilitates timely diagnosis, rational selection of therapeutic strategies, and improvement of clinical outcomes in patients with lung diseases.